Evaluation of Deformation, Mass Loss, and Roughness of Different Metal Burs After Osteotomy for Osseointegrated Implants - Sartori, Elisa Mattias; Shinohara, Elio Hitoshi [UNESP]; Ponzoni, Daniela [UNESP]; Marques Padovan, Luis Eduardo; Valgas, Laiz; Golin, Alexsander Luiz (W B Saunders Co-elsevier Inc, 2012)
Purpose: This study used bovine ribs to comparatively assess the deformation, roughness, and mass loss for 3 different types of surface treatments with burs, used in osteotomies, for the installation of osseointegrated implants.Materials and Methods: The study used 25 bovine ribs and 3 types of helical burs (2.0 mm and 3.0 mm) for osteotomies during implant placement (a steel bur [G1], a bur with tungsten carbide film coating in a carbon matrix [G2], and a zirconia bur [G3]), which were subdivided into 5 subgroups: 1, 2, 3, 4, and 5, corresponding to 0, 10, 20, 30, and 40 perforations, respectively. The surface roughness (mean roughness [Ra], partial roughness, and maximum roughness) and mass (in grams) of all the burs were measured, and the burs were analyzed in a scanning electron microscope before and after use. Data were tabulated and statistically analyzed by use of the Kruskal-Wallis test, and when a statistically significant difference was found, the Dunn test was used.Results: There was a loss of mass in all groups (G1, G2, and G3), and this loss was gradual, according to the number of perforations made (1, 2, 3, 4, and 5). However, this difference was not statistically significant (P < .05). Regarding the roughness, G3 presented an increase in Ra, partial roughness, and maximum roughness (P < .05) compared with G2 and an increase in Ra compared with G1. There was no statistically significant difference (P > .05) between G1 and G2. The scanning electron microscopy analysis found areas of deformation in all the 2.0-mm samples, with loss of substrates, and this characteristic was more frequent in G3.Conclusions: The 2.0-mm zirconia burs had a greater loss of substrates and abrasive wear in the cutting area. They also presented an increased roughness when compared with the steel and the tungsten carbide coating film in carbon matrix. There was no statistically significant difference (P < .05) between G1 and G2 in any mechanical test carried out. (C) 2012 American Association of Oral and Maxillofacial Surgeons J Oral Maxillofac Surg 70:e608-e621, 2012